IgE Immunotherapy Against Cancer - Leoh, Lai Sum (Curr Top Microbiol Immunol, 2015)
The success of antibody therapy in cancer is consistent with the ability of these molecules to activate immune responses against tumors. Experience in clinical applications, antibody design, and advancement in technology have enabled antibodies to be engineered with enhanced efficacy against cancer cells. This allows re-evaluation of current antibody approaches dominated by antibodies of the IgG class with a new light. Antibodies of the IgE class play a central role in allergic reactions and have many properties that may be advantageous for cancer therapy. IgE-based active and passive immunotherapeutic approaches have been shown to be effective in both in vitro and in vivo models of cancer, suggesting the potential use of these approaches in humans. Further studies on the anticancer efficacy and safety profile of these IgE-based approaches are warranted in preparation for translation toward clinical application.